Using method of undetermined coefficients solve y''-2y'+ y = e x + x
in Algebra 1 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

The presence of eˣ on the right-hand side tells us that y(x) must contain eˣ. The differential expression on the left tends to eliminate terms containing eˣ, so let’s see what happens if we just consider the eˣ term alone and come back to the whole of the right-hand expression later.

Let y=p(x)eˣ, where p is a function of x, and consider its derivatives.

Dy or y'=p'(x)eˣ+p(x)eˣ, D²y or y''=p''(x)eˣ+2p'(x)eˣ+p(x)eˣ.

Now we apply the differential expression y''-2y'+y and we get:

p''(x)eˣ+2p'(x)eˣ+p(x)eˣ-2p'(x)eˣ-2p(x)eˣ+p(x)eˣ.

All the terms cancel except for p''(x), and this must evaluate to eˣ.

Therefore p''(x)=1, which we can integrate: p'(x)=x+a where a is a constant, p(x)=x²/2+ax+b, where b is another constant. Therefore y=eˣ(x²/2+ax+b).

Now we have to find out how to get the x term in eˣ+x. Let this term be q(x) where q is another function.

q''(x)-2q'(x)+q(x)=x. If q''(x)=0, q'(x)=c and q(x)=cx+d. We can see that c=1 because we have to end up with 1x. Now we have y=eˣ(½x²+ax+b)+x+d with undetermined constants.

Now we can apply the differential expression to this:

x+d-2+eˣ=eˣ+x, therefore d=2 and y=eˣ(½x²+ax+b)+x+2.

by Top Rated User (642k points)

Related questions

1 answer
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
82,892 questions
87,494 answers
1,964 comments
3,930 users